Analysis of Production Affecting Factors Milkfish (Chanos chanos) In Muna Regency - Sinaini, La; Azi, Mulyati (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This study aims to identify the factors that affect the production of Chanos chanos in Muna Regency. The research data used in this study is cross-section data is data that describes the state at a given time. The number of samples taken in this study was 35 farmers. The analytical tool used is an analysis of the Cobb-Douglass production function that calculations using the multiple linear regression equation. The results showed that the variable pond area, labor, feed, TSP fertilizer, phonsca NPK fertilizer, and seed have a significant impact on Chanos chanos production in Muna Regency. Suggestions that can be submitted from the results of research are for farmers, to increase their production, they need to increase the area of aquaculture ponds, increase labor for maintenance, increase the use of TSP fertilizers, decrease the use of phonsca NPK fertilizers, efficient use of seeds, reduce artificial feeding by maximizing the use of natural feed, and conducting cultivation Chanos chanos using cultivation technology correctly, for related institutions intensifying the extension of Chanos chanos cultivation technology activities, as well as facilitating farmers to increase pond area, and access to business capital, for subsequent research it is recommended to conduct research by adding other factors not included in the research model.